1995
DOI: 10.1034/j.1399-3054.1995.930432.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to sucrose and glutamine by soybean embryos grown in vitro

Abstract: 1995. Responses to sucrose and glutamine by soybean embryos grown in vitro Immature soybean {Giycine max [L,| Merr. cv. Ransom) embryos were grown in vitro in the presence of different concentrations of sucrose and glutamine to examine how availability of carbohydrate and nitrogen affects dr>' matter accumulation and embryo composition. Embrvos were transferred to fresh medium every 4 days to maintain sucrose and glutamine concentrations of the culture medium. In all experiments, aecumulalion of dry matter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…To carry out the study, the sucrose concentration was used in 204.49 mM culture medium in order to prevent the precocious germination (Obendorf and Wettlaufer, 1984). Saravitz and Raper (1995) reported (in vitro studies), that the highest fresh weight accumulation was obtained at 150 mM of sucrose, and when sucrose limited the growth, soybean seed was capable of using glutamine as a source of energy source and also as a source of N. In accordance with the results obtained by Pípolo et al (2004b), the glutamine concentration afftected the composition of soybean seeds. Protein percentage in the seed increased when there was an increase in the glutamine concentration in the cultivation in vitro (Table 2), and there was a statistical difference (P<0.05) in the same cultivar, which happened in both CD 206 and CD 202 cultivars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To carry out the study, the sucrose concentration was used in 204.49 mM culture medium in order to prevent the precocious germination (Obendorf and Wettlaufer, 1984). Saravitz and Raper (1995) reported (in vitro studies), that the highest fresh weight accumulation was obtained at 150 mM of sucrose, and when sucrose limited the growth, soybean seed was capable of using glutamine as a source of energy source and also as a source of N. In accordance with the results obtained by Pípolo et al (2004b), the glutamine concentration afftected the composition of soybean seeds. Protein percentage in the seed increased when there was an increase in the glutamine concentration in the cultivation in vitro (Table 2), and there was a statistical difference (P<0.05) in the same cultivar, which happened in both CD 206 and CD 202 cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Thompson et al (1977) and Obendorf et al (1984) have described the success obtained with soybean seeds cultured in situ and in vitro. Those studies represented a major advance to understand the development of soybean seeds in vitro, including: 1) estimates on the effect of temperature on the seed's growth rate (Egli and Wardlaw, 1980;Pípolo et al, 2004a); 2) the relationship among genetic differences, seed's growth rate and the numbers of cotyledon cells (Egli et al, 1981); 3) synthesis of storage protein ; 4) use of ureids, amid and amino acids for the synthesis of protein in soybean immature cotyledons Rainbird et al, 1984;Holowash et al, 1984;Haga and Sodek, 1987;Wettlaufer and Obendorf, 1991); 5) growing and composition rates of soybean seeds affected by the supply of carbohydrate and/or nitrogen assimilated by the seed (Saravitz andRaper, 1995, Hayati et al, 1996;Pípolo et al, 2004b). Obendorf et al (1984) also demonstrated that, provided with a simple set of materials, the soybean seeds grew regularly.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that high and low carbon supply relative to nitrogen accelerates and decelerates oil synthetic rate, respectively (Saravitz and Raper, 1995;Pipolo et al, 2004), we assumed that the significant decline in seed oil content resulting from the inactivation of SnRK2.6 might be partly attributable to the role of this kinase in the control of either carbon assimilation in the source leaves or carbon translocation into the sink tissue or both. To provide evidence for the role of SnRK2.6 in carbon assimilation, we investigated if inactivation of SnRK2.6 could alter the steady-state levels of leaf soluble sugars and starch under wellwatered conditions.…”
Section: Snrk26 Imparts Carbon Source and Sink Strength Through Regumentioning
confidence: 99%
“…Triacylglycerol serves as a carbon and energy storage reservoir, and high energy load and fatty acid supply are thought to favor triacylglycerol synthesis. The high and low carbon level relative to nitro-gen accelerates and decelerates oil synthetic rate, respectively (Saravitz and Raper, 1995;Pipolo et al, 2004). This implies that alteration in seed oil synthesis may signify, to a large extent, the status of sugar and energy supply from the source tissue in oilseed plants.…”
mentioning
confidence: 99%
“…With a view to soybean embryo proliferation, 1 g/l asparagine was included in the formulation of the original FN liquid medium (Finer & Nagasawa, 1988), and it was also used in the FN Lite proliferation medium (Samoylov et al, 1998a) and FNL histodifferentiation/maturation medium (Samoylov et al, 1998b). On the other hand, culture media supplemented with glutamine were shown to be beneficial to zygotic soybean embryos (Thompson et al, 1977), by increasing embryo size (Lippmann & Lippmann, 1993;Dyer et al, 1987), and inducing storage oil and protein synthesis (Saravitz & Raper, 1995). Schmidt et al (2005) compared the effect of FNLS3S3 supplemented with asparagine or glutamine on embryo histodifferentiation/maturation.…”
Section: Amino Acidsmentioning
confidence: 99%